2020
DOI: 10.1039/d0fo00461h
|View full text |Cite
|
Sign up to set email alerts
|

Effects of inulin on protein in frozen dough during frozen storage

Abstract: Effects of inulin on protein in frozen dough during frozen storage was investigated by sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE), fourier transform infrared spectroscopy (FTIR), differential scanning calorimeter (DSC) and...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(11 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…Furthermore, there is also a need to freeze dough as it is a convenient and cost‐effective way to meet the nutritional needs of people who are pressed for time and do not have access to various food sources such as travelers, mountaineers, astronauts, and soldiers (Rahman, 2007). However, this procedure is associated with adverse changes in the technological characteristics of wheat bread, including a reduction in specific volume, increased fermentation time, and a weakening of the gluten network structure (Ke et al, 2020). Hence, it is challenging to fortify white wheat bread and simulate gluten structure in gluten‐free bread.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, there is also a need to freeze dough as it is a convenient and cost‐effective way to meet the nutritional needs of people who are pressed for time and do not have access to various food sources such as travelers, mountaineers, astronauts, and soldiers (Rahman, 2007). However, this procedure is associated with adverse changes in the technological characteristics of wheat bread, including a reduction in specific volume, increased fermentation time, and a weakening of the gluten network structure (Ke et al, 2020). Hence, it is challenging to fortify white wheat bread and simulate gluten structure in gluten‐free bread.…”
Section: Introductionmentioning
confidence: 99%
“…It can be clearly seen that after 7 days of storage the intensity of the band at 1670 cm −1 increased, which may be the result of hydrogen bond interaction in protein molecules. 37 Therefore, MLP showed a positive effect on inhibiting bread staling.…”
Section: Long-range Ordered Structurementioning
confidence: 98%
“…Moreover, the MP solubility of CMCO-B group was higher than that of CMCO-A at the same storage time. It has been shown that the complexity of hydrogen bonding enhanced in the food matrix as the DS of charged polysaccharide increased [20,36]; thus, water molecules became more bounded to the protein networks, which led to a better cryoprotective effect to the MP, i.e., CMCO-B group > CMCO-A group, whose content of salt-soluble protein was 70 and 62 mg/g, respectively.…”
Section: Salt-soluble Protein Contentmentioning
confidence: 99%